Вплив основних агротехнічних прийомів на продуктивність посівів ріпаку озимого в Північному Степу України - Яцканич, Михайло Вікторович; Yatskanych, Mykhailo (ЦНТУ, 2024)
Основна мета роботи - визначити та рекомендувати сільськогосподарському виробництву агротехнічні прийоми, які забезпечують формування високої продуктивності ріпаку озимого та високу економічну ефективність його вирощування. На основі отриманих результатів проведеного дослідження та економічного аналізу ПрАТ «Олексіївське» рекомендуємо розширити посівні площі ріпаку озимого Ексепшн та Арізона. Вони забезпечують найбільш високу врожайність та економічну ефективність вирощування ріпаку озимого. The main objective of the work is to identify and recommend agro-technical practices to agricultural production that ensure the formation of high productivity of winter rapeseed and high economic efficiency in its cultivation. Based on the results of the conducted research and economic analysis of the agricultural enterprise "Oleksiivske", we recommend expanding the sowing areas of winter rapeseed varieties Exception and Arizona. These varieties provide the highest yield and economic efficiency in the cultivation of winter rapeseed.
The influence of basic agrotechnical techniques on the productivity of winter rapeseed crops in the Northern Steppe of Ukraine
Keywords: ріпак; строки сівби; способи сівби; turnip; sowing dates; sowing methods